Agranulocytosis with deferiprone treatment of superficial siderosis. (7th August 2013) - Huprikar, Nikhil; Gossweiler, Marisa; Callaghan, Maureen; Bunge, Paul
Abstract : Superficial siderosis of the central nervous system is a rare neurological disorder caused by deposits of haemosiderin on subplial brain matter. Characterised by a thin dark layer surrounding the brain stem, cerebellum and cortical fissures on the T2-weighted MRI, symptoms include sensorineural hearing loss and progressive gait ataxia. A specific aetiology for the blood in the subarachnoid space is identified in less than 50% of cases. While identification of a specific vascular defect allows for vascular repair, treatment options are limited for idiopathic superficial siderosis. Recently, a pilot safety study demonstrated promising results using an iron chelator, deferiprone. While this approach is promising, we present a potential serious complication of this therapy—the first report of agranulocytosis in the treatment of superficial siderosis following deferiprone therapy.